Development of Critical Thinking and Logical Argumentation Assessment Instruments for Students in Problem-Based Learning - Muhammad Khoirul Fikri; Rusijono Rusijono; Khusnul Khotimah (Journal of Educational Sciences, 2026)
The background of this study is the demand of the Industrial Revolution 4.0 for Higher Order Thinking Skills (HOTS), particularly critical thinking and logical argumentation among university students. Problem-Based Learning (PBL) is recognized as effective in developing these skills; however, valid and comprehensive assessment instruments, especially in essay form, remain limited. This study aims to develop and examine the quality of an essay test instrument to measure students' critical thinking and logical argumentation skills within PBL in the Logic and Critical Thinking Methods course. The method employed was Research and Development (R&D), adapting a simplified Borg and Gall model, which included needs analysis, test blueprint design, item development, expert validation, empirical try-outs, and item quality analysis. The research subjects were 55 students in Surabaya. Expert validation using Aiken's V showed an average coefficient of 0.81, categorized as very high. Construct validity testing using item-total correlation confirmed that all items were valid, and reliability testing using Cronbach's Alpha yielded a coefficient of 0.768, indicating high reliability. Item quality analysis revealed that most items possessed moderate difficulty and high discrimination power. In conclusion, the developed instrument is valid, reliable, and suitable for use as a measurement tool for assessing students' critical thinking and logical argumentation abilities in a PBL context.